2003
DOI: 10.1111/j.1582-4934.2003.tb00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells from hematopoietic stem cells are functionally different from those of human umbilical vein

Abstract: Hematopoietic stem cells have a remarkable plastic capacity, which allows them to differentiate into various cells, such as immune cells, nervous cells, muscle cells, bone and cartilaginous cells. The aim of this study was to show the capacity of stem cells to differentiate into endothelial cells, in culture, after addition of endothelial cells growth suplement (ECGS). We also compared the behavior of these cells with that of endothelial cells obtained from human umbilical vein (HUVEC). CD34+ cells obtained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…These findings may well be explained by a dose-dependent mechanism, which varies according to studies and different cell types. It has been shown that endothelial cells in different anatomic regions of the same patient are structurally and functionally dissimilar [43][44][45][46]. This regional endothelial cell dysfunction may be the disease pathway for several different disease processes where systemic genetic profiles interact with regional endothelial gene function and protein expression.…”
Section: Discussionmentioning
confidence: 97%
“…These findings may well be explained by a dose-dependent mechanism, which varies according to studies and different cell types. It has been shown that endothelial cells in different anatomic regions of the same patient are structurally and functionally dissimilar [43][44][45][46]. This regional endothelial cell dysfunction may be the disease pathway for several different disease processes where systemic genetic profiles interact with regional endothelial gene function and protein expression.…”
Section: Discussionmentioning
confidence: 97%
“…Several groups have reported that EPC-derived cells cannot function as mature ECs. Paunescu et al [26] documented that EPCs from human umbilical cord blood differed functionally from HUVECs, as the former show a different reaction to TNF compared with mature ECs. Another study demonstrated that bone marrow-derived cells may not be incorporated into the vessel wall in vivo but only promote angiogenesis by excretion of certain factors, such as FGF-2, VEGF and MCP-1 [27].…”
Section: Discussionmentioning
confidence: 99%
“…Croix et al 2000). Heterogeneity of ECs according to tissuespecific vascular-bed hemostasis has become an accepted concept in vascular biology (Aird 2003;Paunescu et al 2003;Garlanda and Dejana 1997). Hence, it seems to be more appropriate to study specifically ECs isolated from the affected tissue in a vascular disease state rather than using primary endothelial cells from another origin, such as HUVECs, or an EC line.…”
Section: Discussionmentioning
confidence: 99%